Toxicokinetics of titanium dioxide (TiO2) nanoparticles after inhalation in rats. (4th January 2017) - Pujalté, Igor; Dieme, Denis; Haddad, Sami; Serventi, Alessandra Maria; Bouchard, Michèle
Highlights: The kinetics of TiO2 nanoparticles was studied in rats after a 6-h inhalation. TiO2 persisted in lungs, where highest tissue levels were found. TiO2 in lungs reached peak values only at 48 h and levels decreased over 14 days. Fecal amounts suggest a mucociliary clearance of inhaled NPs and ingestion. A certain translocation to the olfactory bulb and the brain was also observed. Abstract: This study focused on the generation of aerosols of titanium dioxide (TiO2 ) nanoparticles (NPs) and their disposition kinetics in rats. Male Sprague-Dawley rats were exposed by inhalation to 15 mg/m 3 of anatase TiO2 NPs (∼20 nm) during 6 h. Rats were sacrificed at different time points over 14 days following the onset of inhalation. Ti levels were quantified by ICP-MS in blood, tissues, and excreta. Oxidative damages were also monitored (MDA). Highest tissue levels of Ti were found in lungs; peak values were reached only at 48 h followed by a progressive decrease over 14 days, suggesting a persistence of NPs at the site-of-entry. Levels reached in blood, lymph nodes and other internal organs (including liver, kidney, spleen) were circa one order of magnitude lower than in lungs, but the profiles were indicative of a certain translocation to the systemic circulation. Large amounts were recovered in feces compared to urine, suggesting that inhaled NPs were eliminated mainly by mucociliary clearance and ingested. TiO2 NPs also appeared to be partly transferred to olfactory bulbs and brain. MDA levels indicative of oxidative damage were significantly increased in lungs and blood at 24 h but this was not clearly reflected at later times. Translocation and clearance rates of inhaled NPs under different realistic exposure conditions should be further documented.